Characterising the alternative and polar questions of Irish - Nolan, Brian (LingBaW. Linguistics Beyond and Within, 2020)
This paper gives an account of the similarities and differences between alternative and polar questions, where these question forms stand at the intersection of syntax, semantics, and pragmatics. We contrastively examine the nature of alternative and polar yes-no questions. We characterise the forms of these question types and the functions they serve. We examine the semantic and pragmatic dimensions of each question form and their answers. We characterise the felicity conditions necessary for their successful realisation of the speech act of requesting information via the alternative and yes-no interrogatives and assume that information is freely exchanged under a Gricean presumption of cooperation. We show that alternative questions have some similarities, but also significant differences, to polar yes-no questions. Alternative questions do not allow for yes-no answers. Instead, an appropriate answer must contain one of a selection from the alternative choice options listed in the framing of the question. Alternative questions are dependent on the presence of disjunction. We characterise the syntax and semantics of polar yes-no questions. We demonstrate in respect of the answers to polar yes-no questions of Irish that they contain instances of ellipsis and are full clausal expressions with a complete semantics where the elided elements are from the question part of the question-answer pair. The propositional content of polar yes-no questions is inferred from the context, specifically from the question with which the answer is paired. Irish does not have any exact words which directly correspond to English ‘yes’ or ‘no’ and so employs different strategies where a yes-no answer is required.